Analisis Fonologis pada Penderita Down Syndrome dalam Pembacaan Al-Quran: Studi Kasus pada Surat Ali-Imran - Nurfitri, Hanifah (STAI Syaichona Moh. Cholil Bangkalan, 2024)
This study examines the phonological challenges faced by individuals with Down Syndrome in reciting Surah Ali-Imran. This topic was raised to understand how Down Syndrome limitations affect phonological abilities in reciting the Qur'an. This study used a qualitative research method with a case study design. Data were obtained through observation and analysis of recitation recordings to identify phonological errors. The main results of the study indicate that individuals with Down Syndrome tend to experience errors in the form of sound substitutions, letter omissions, and errors in the application of long-short harakat. The causative factors include cognitive limitations, speech motor disorders, and the complexity of Arabic phonology. These findings provide an important contribution to the development of a more inclusive, adaptive, and appropriate Qur'an teaching method for individuals with Down Syndrome. In addition, this study is useful for families, teachers, and Islamic educational institutions in understanding the challenges faced and creating more effective strategies for learning the Qur'an for individuals with Down syndrome.